Bariatric surgery as a treatment of polycystic ovary syndrome: a systematic review and meta-analysis - Mirghani, Hyder; Shaman, Amani (Frontiers in Endocrinology, 2026)
BackgroundPolycystic ovary syndrome (PCOS) is the most common endocrine disorder among females of reproductive age, and the majority are obese/overweight. PCOS management, including lifestyle and drugs, is limited by unsustainability and side effects. Bariatric surgery (BS) is promising in addressing hyperandrogenism and pregnancy outcomes. We aimed to assess the impact of bariatric surgery on PCOS components.MethodsWe systematically searched PubMed/MEDLINE, Google Scholar, Cochrane Library, and Web of Science during July and August 2025, articles from inception up to August 2025 were included. The keywords used were BS, sleeve gastrectomy, gastric bypass, gastric banding, menstrual irregularities, free testosterone, total testosterone, hirsutism, SHBG, lutenizing hormone, antimullarian hormone (AMH), follicle-stimulating hormone, and pre-term deliveries. 648 articles were eligible, 35 full texts were reviewed, and 27 were included in the final meta-analysis.ResultsBariatric surgery reduced menstrual irregularities and hirsutism, with odds ratios of 27.68, 95% CI, 9.83-78.00, and 6.61, 95% CI, 0.97-47.07, respectively. In addition, total testosterone, free testosterone, AMH, and LH were reduced, SD, -19.95, 95% CI, -28.53–11.38, SD, 2.40, 95% CI, 1.30.53-3.51, SD, 1.66, 95% CI, 0.17-3.14, and SD, 2.21, 95% CI, 1.73-2.69 respectively, while SHBG were increased. No effects were observed regarding FSH, birth weight, gestational age, and pre-term delivery.ConclusionBS reduced menstrual irregularities, hirsutism, total and free testosterone, AMH, and LH and increased SHBG. No significant differences were evident regarding other outcomes. Larger controlled trials investigating the long-term effects and the mechanism of action of BS on pregnancy outcomes, metabolic, and reproductive hormones are needed.